Electrochemical devices and electronic devices

By controlling the mass percentage of the electrolyte content and adding sulfur-containing and fluorine-containing additives in the lithium-ion battery, a stable SEI film is formed, which solves the safety and circulation performance problems of lithium-ion batteries under high-voltage density conditions, and achieves higher circulation and safety performance.

CN115380415BActive Publication Date: 2025-02-28NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280003190.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-28
Publication Date
2025-02-28
Estimated Expiration
2042-01-28

AI Technical Summary

Technical Problem

Under high pressure tight conditions, high liquid retention volume will bring safety problems and circulation performance attenuation problems.

Method used

By controlling the mass percentage of the electrolyte content between 2% and 8%, and adding sulfur-containing substances and fluorine-containing additives in the valence of S4+/S6+ or above to the electrolyte, a stable high-ion-conducting solid electrolyte interface (SEI) film is formed to reduce electrolyte consumption.

Benefits of technology

Under low liquid injection conditions, the circulation and safety performance of lithium-ion batteries are improved and the service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003851471580000011
    Figure BDA0003851471580000011
  • Figure BDA0003851471580000021
    Figure BDA0003851471580000021
  • Figure BDA0003851471580000091
    Figure BDA0003851471580000091
Patent Text Reader

Abstract

Provided is an electrochemical device and an electronic device, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the electrolyte accounts for 2% to 8% of the total mass of the battery cell; the electrolyte contains S 4+ / S 6+ The sulfur-containing substances in the above valence states have a mass percentage B of 10% to 20% based on the total mass of the electrolyte. By adjusting the mass percentage of the electrolyte, the use of sulfur-containing substances and fluorine-containing additives, the ion conductivity of the SEI membrane is improved, the electrolyte consumption is reduced during the cycle, the injection volume is reduced, and the safety performance and cycle performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device. Background Art

[0002] Lithium-ion batteries have the characteristics of high specific energy, high operating voltage, low self-discharge rate, small size and light weight, and are widely used in various fields such as power storage, portable electronic devices and electric vehicles. As the scope of use of lithium-ion batteries continues to expand, the market has put forward higher requirements for lithium-ion batteries, such as requiring lithium-ion batteries to have faster charging speed and longer service life.

[0003] The electrolyte retention volume has a great influence on the cycle performance of lithium-ion batteries. Under high-pressure and high-density conditions, high electrolyte retention will bring more safety issues and challenges, while reducing the electrolyte content will lead to the problem of cycle performance degradation. Summary of the invention

[0004] The purpose of this application is to provide an electrochemical device and an electronic device to improve the cycle performance of the electrochemical device. The specific technical solution is as follows:

[0005] In a first aspect, the present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the mass percentage A of the electrolyte mass to the total mass of the battery core is 2% to 8%, for example, A can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8% or any range therebetween; the electrolyte contains S 4+ / S 6+ The sulfur-containing substances in the above valence states, based on the total mass of the electrolyte, have a mass percentage B of 10% to 20%. For example, B can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any range therebetween.

[0006] The total mass of the battery core is the mass of the electrochemical device except the packaging structure.

[0007] The inventors of the present application have found that controlling the mass percentage of the electrolyte and the content of S 4+ / S 6+ The mass percentage of the valence film-forming additive is within the scope of the present application, which can form a stable high ion conductivity solid electrolyte interface (SEI) film at the negative electrode, reduce electrolyte consumption during the cycle, and improve the cycle performance and safety performance of the electrochemical device under the condition of low injection volume.

[0008] In one embodiment of the present application, the sulfur-containing substance is selected from at least one of the compounds of the following formula:

[0009]

[0010] in,

[0011] R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 Each independently selected from C 1 To C 10 Saturated hydrocarbon, C 2 To C 10 Unsaturated hydrocarbon group, C 1 To C 10 Haloalkyl, C 2 To C 10 Halogenated alkenyl, C 2 To C 10 Haloalkynyl, C 6 To C 26 Any of aryl, -F, -Cl, -H;

[0012] R 1 and R 2 , R 3 and R 4 , R 5 and R 6 , R 7 and R 8 Can be connected into a ring.

[0013] Without being limited to any theory, the applicant has found through research that when the above-mentioned sulfur-containing substances are selected, the cycle performance and safety performance of the electrochemical device can be further improved.

[0014] In one embodiment of the present application, the sulfur-containing substance includes at least one of 2,4-butane sultone, 1,3-propane sultone, vinyl sulfite, propylene sulfite, dimethyl sulfite, and diethyl sulfite. Without being limited to any theory, the applicant has found through research that when the above sulfur-containing substances are selected, the cycle performance and safety performance of the electrochemical device can be further improved.

[0015] In one embodiment of the present application, the electrolyte includes a fluorine-containing additive, and based on the total mass of the electrolyte, the mass percentage C of the fluorine-containing additive is 15% to 30%, for example, C can be 15%, 18%, 21%, 24%, 27%, 30% or any range therebetween. The applicant has found through research that by controlling the mass percentage of the fluorine-containing additive within the scope of the present application, it is beneficial to generate a stable and highly ion-conductive SEI film at the negative electrode, thereby improving the cycle performance and safety performance of the electrochemical device.

[0016] In one embodiment of the present application, the fluorine-containing additive is selected from at least one of the compounds of the following formula:

[0017]

[0018] in,

[0019] X 1 , X 2 , X 3 , X 4 , X 5 , X 6 Each independently selected from C 1 To C 10 Fluorinated saturated hydrocarbon, C 2 To C 10 Fluorinated unsaturated hydrocarbon group, C 1 To C 10 Haloalkyl, C 2 To C 10 Halogenated alkenyl, C 2 To C 10 Haloalkynyl, C 6 To C 26 Any of aryl, -F, -H;

[0020] Y 1 Selected from P, B, O, N or S;

[0021] Y 2 , Y 3 Each independently selected from C 1 To C 10 Fluorinated saturated hydrocarbon, C 2 To C 10 Any one of fluorinated unsaturated hydrocarbon group, P, B, O, S, and N;

[0022] X 1 and X 2 , X 3 and X 4 , X 5 and X 6 and Y 2 and Y 3At least one of them is a fluorine-containing group;

[0023] X 1 and X 2 , X 3 and X 4 , X 5 and X 6 and Y 2 and Y 3 Can be connected into a ring.

[0024] Without being limited to any theory, the applicant has found that by selecting the above-mentioned fluorine-containing additives, the cycle performance and safety performance of the electrochemical device can be further improved.

[0025] In one embodiment of the present application, the fluorine-containing additive includes at least one of fluoroethylene carbonate, fluoroethyl methyl carbonate, fluorodimethyl carbonate, fluorodiethyl carbonate, fluoroethyl propionate, fluoropropyl propionate, fluoroethyl acetate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalate borate, lithium tetrafluoroborate, lithium trifluoromethylsulfonate and lithium difluorophosphate. When the fluorine-containing additive is a fluorine-containing lithium salt, the mass percentage of the fluorine-containing lithium salt is 10% to 30% based on the total mass of the electrolyte, for example, it can be 10%, 12%, 15%, 18%, 21%, 24%, 27%, 30% or any range therebetween. Without being limited to any theory, the applicant has found that by selecting the above-mentioned fluorine-containing additive, the cycle performance and safety performance of the electrochemical device can be further improved.

[0026] In one embodiment of the present application, the porosity of the positive electrode sheet is D%, and the value range of D is 5≤D≤35, for example, D can be 5, 10, 15, 20, 25, 30, 35 or any range therebetween, wherein the relationship between D% and A% is as follows: 0.5≤D% / A%≤15, for example, D% / A% can be 0.5, 1, 3, 5, 7, 9, 12, 15 or any range therebetween. The applicant has found through research that by controlling the porosity of the positive electrode sheet within the above range, the porosity and the mass percentage of the electrolyte are controlled in a coordinated manner, and under high pressure and density conditions, the electrolyte fully wets the pores, can provide sufficient electron paths, and has no more by-products, thereby improving the cycle performance and safety performance of the electrochemical device.

[0027] In one embodiment of the present application, the sum of the mass percentage of sulfur element and the mass percentage of fluorine element in the SEI film on the surface of the negative electrode plate is E%, wherein 10≤E≤50, for example, E can be 10, 15, 20, 25, 30, 35, 40, 45, 50 or any range therebetween. The applicant has found through research that when the E value is too high (for example, E is greater than 50), the interface dynamics of the electrochemical device deteriorates, and the cycle performance deteriorates; when the E value is too low (for example, E is less than 10), the stability of the SEI film decreases, and the cycle performance and safety performance deteriorate. By controlling the E value within the above range, the cycle performance and safety performance of the electrochemical device can be further improved.

[0028] The second aspect of the present application provides an electronic device, comprising the electrochemical device provided by the first aspect of the present application. Since the electrochemical device of the present application has good cycle performance and safety performance, the electronic device provided by the present application has a long service life and good performance.

[0029] The present application provides an electrochemical device and an electronic device, which improve the ionic conductivity of the SEI membrane by regulating the mass percentage of the electrolyte in the electrochemical device, the use of sulfur-containing substances and fluorine-containing additives, reduce the electrolyte consumption during the cycle, limit the relationship between porosity and electrolyte retention volume, and improve safety performance and cycle performance while reducing the injection volume. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the present application is further described in detail with reference to the embodiments below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of this application.

[0031] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.

[0032] There is no particular limitation on the positive electrode sheet in the present application, as long as the purpose of the present application can be achieved. The positive electrode sheet generally comprises a positive current collector and a positive active material. The above-mentioned positive current collector is not particularly limited, and may be any positive current collector known in the art, such as aluminum foil, aluminum alloy foil, and composite current collector. The above-mentioned positive active material is not particularly limited, and may be any positive active material of the prior art, for example, it may include at least one of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, or lithium iron manganese phosphate.

[0033] In the present application, the thickness of the positive electrode current collector and the positive electrode active material is not particularly limited as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 8 μm to 12 μm, and the thickness of the positive electrode active material is 30 μm to 120 μm.

[0034] In the present application, the positive electrode material layer may also include a conductive agent, and the present application has no particular restrictions on the conductive agent, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials or conductive polymers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole.

[0035] Optionally, the positive electrode may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a commonly used conductive layer in the art, for example, including but not limited to the above conductive agent and the above binder.

[0036] The negative electrode current collector in the present application is not particularly limited, and materials such as metal foil or porous metal plate can be used, such as foil or porous plate of metals such as copper, nickel, titanium or iron or their alloys, such as copper foil. The negative electrode active material layer includes a negative electrode active material, a conductive agent, a binder and a thickener. The binder can be at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin or carboxymethyl cellulose (CMC); the thickener can be carboxymethyl cellulose.

[0037] In the present application, the negative electrode material layer may further include a conductive agent. The present application has no particular limitation on the conductive agent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of the above conductive agents.

[0038] In the present application, the negative electrode material layer may further include a binder. The present application has no particular limitation on the binder, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of the above-mentioned binders.

[0039] Optionally, the negative electrode may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular limitation on the composition of the conductive layer, which may be a commonly used conductive layer in the art, and may include but is not limited to the above conductive agent and the above binder.

[0040] There is no particular limitation on the separator in the present application, as long as the purpose of the present application can be achieved, and the separator substrate can be selected from at least one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polyimide (PI) or aramid. For example, polyethylene includes at least one component selected from high-density polyethylene, low-density polyethylene and ultra-high molecular weight polyethylene. Especially polyethylene and polypropylene, they have excellent effects on preventing short circuits and can improve the stability of electrochemical devices through the shutdown effect. The separator of the present application can have a porous structure, and the size of the pore size is not particularly limited, as long as the purpose of the present application can be achieved, for example, the size of the pore size can be 0.01μm to 1μm. In the present application, the thickness of the separator is not particularly limited, as long as the purpose of the present application can be achieved, for example, the thickness can be 5μm to 500μm.

[0041] In the present application, the electrolyte may also include a non-aqueous solvent. The present application has no particular restrictions on the non-aqueous solvent, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds or cyclic carbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The above-mentioned cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone, mevalonolactone or caprolactone. The ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate ester. The total mass percentage of the other non-aqueous solvents based on the total mass of the electrolyte is 10% to 80%, for example, 10%, 15%, 20%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any range therebetween.

[0042] In the present application, the electrolyte may further include a lithium salt, the lithium salt including but not limited to at least one of lithium hexafluorophosphate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium trifluoromethylsulfonate, lithium difluorophosphate, lithium hexafluoroarsenate, lithium dioxalate borate, and lithium perchlorate. The present application has no particular restriction on the mass percentage of the lithium salt, as long as the purpose of the present application can be achieved. Based on the total mass of the electrolyte, the total mass percentage of the lithium salt is 10% to 37.5%, for example, it can be 10%, 12%, 14%, 16%, 18%, 20%, 30%, 37.5% or any range therebetween. When the fluorine-containing lithium salt is used as both a fluorine-containing additive and a lithium salt, the mass percentage of the fluorine-containing lithium salt is 10% to 30%, for example, it can be 10%, 12%, 14%, 16%, 18%, 20%, 30% or any range therebetween.

[0043] The electronic device in the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0044] The preparation process of the electrochemical device is well known to those skilled in the art and is not particularly limited in this application. For example, a lithium-ion battery can be manufactured by overlapping the positive electrode and the negative electrode via a separator, and placing them in a housing after winding, folding, etc. as required, injecting an electrolyte into the housing and sealing it. In addition, an overcurrent protection element, a guide plate, etc. can also be placed in the housing as required to prevent the pressure inside the lithium-ion battery from rising and overcharging and discharging.

[0045] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0046] Specific test methods and equipment

[0047] Cycle test method:

[0048] Place the lithium-ion battery in a constant temperature box at 25°C, charge it to 4.5V at a constant current of 0.5C, charge it to 0.05C at a constant voltage, and then discharge it to 3.0V at a constant current of 1.0C. This is a charge and discharge cycle. Perform 500 cycle charge and discharge tests in the above manner to monitor the capacity retention rate.

[0049] Capacity retention rate = [remaining discharge capacity / initial discharge capacity] × 100%.

[0050] Hot box test method:

[0051] Charge the lithium-ion battery at 0.5C constant current to 4.2V at 20±5℃, and charge it at 4.2V at constant voltage to 0.05C. Set the furnace temperature to 25℃. After standing for 30 minutes, start heating at a rate of 5±2℃ / min to the specified temperature±2℃, and maintain it for 60 minutes. Monitor the changes in voltage, lithium-ion battery surface temperature, furnace temperature, and whether there is leakage, fire, or explosion during the process.

[0052] Drop test method:

[0053] Charge the lithium-ion battery to 4.2V at 0.5C constant current at 20±5℃, charge to 0.05C at 4.2V constant voltage, and drop it freely from a height of 1.5 meters onto a smooth marble surface; drop sequence: front-back-bottom-top-left-right-upper left-upper right-lower left-lower right, drop each side / corner once in a row as one round, check the battery, drop 10 rounds in total. Record the changes in the voltage and internal resistance voltage of the lithium-ion battery after the test, the surface temperature of the lithium-ion battery, and whether it leaks, catches fire, or explodes.

[0054] Porosity test method:

[0055] The gas replacement method was used to test the porosity of the positive electrode: the pore volume of the sample was expressed as a percentage of the total volume of the sample, P%.

[0056] The positive electrode to be tested is punched into small discs of fixed size (diameter d = 10 mm) and regular shape. A certain mass of sample pieces is weighed and placed in a true density tester (AccuPyc II 1340). The test system is sealed and inert gas is introduced to obtain the true volume V of the sample. 0 , calculate the apparent volume V according to the area and thickness of the sample piece. The porosity of the pole piece is calculated as follows:

[0057] P%=[(VV 0 ) / V]×100%.

[0058] Electrolyte quality test:

[0059] Disassemble the lithium-ion battery, put it in a sample box, pour dimethyl carbonate (DMC) to completely immerse the battery pole piece in the DMC solution. After soaking for 8 hours, replace it with new DMC and soak overnight (14 hours). Take out the soaked lithium-ion battery and put it in a beaker, and put it in a vacuum drying oven to dry overnight (14 hours). According to the difference in mass of the lithium-ion battery before soaking and after drying, calculate the mass percentage of the electrolyte in the lithium-ion battery:

[0060] Electrolyte mass percentage = electrolyte mass / lithium ion battery mass × 100%.

[0061] Determination method of element content in SEI film:

[0062] In an argon atmosphere glove box with a water content of <10ppm, the lithium-ion battery was discharged and disassembled to obtain the negative electrode. The residual electrolyte on the surface of the electrode was washed with dimethyl carbonate (DMC), dried, and placed in the sample bin of an X-ray photoelectron spectrometer (XPS). The flat surface area of ​​the material particles was selected to test the X-ray photoelectron spectrum. The peak position of C1s was taken as 284.8eV for reference. The peaks appearing in the spectrum were calibrated, and the area was integrated and normalized to obtain the percentage of different elements.

[0063] Example 1

[0064] (1) Preparation of electrolyte

[0065] In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), propylene carbonate (PC), and ethyl propionate (EP) were uniformly mixed at a mass ratio of 1:1:1 to form a base solvent, and then sulfur-containing substances and LiPF were added as shown in Table 1. 6 Dissolve and stir evenly to form an electrolyte. Finally, based on the total mass of the electrolyte, LiPF 6 The mass percentage is 12.5%, and the balance is the base solvent.

[0066] (2) Preparation of positive electrode sheet

[0067] The positive electrode active material is lithium cobalt oxide (LiCoO 2 ), conductive agent acetylene black, binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:2:2, N-methylpyrrolidone (NMP) is added as a solvent, and a slurry with a solid content of 75% is prepared, and the slurry is stirred under the action of a vacuum mixer until the system becomes a uniform positive electrode slurry. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10 μm, and dried at 90°C to obtain a positive electrode sheet with a single-sided coating of positive electrode active material and a positive electrode active material layer thickness of 110 μm. After the above steps are completed, the single-sided coating of the positive electrode sheet is completed. After that, the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet with a double-sided coating of positive electrode active material. After the coating is completed, the positive electrode sheet is cold pressed and cut into a specification of 74mm×867mm for standby use. After testing, the porosity of the positive electrode sheet is 15%.

[0068] (3) Preparation of negative electrode sheet

[0069] The negative electrode active material graphite, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are mixed in a weight ratio of 97.4:1.4:1.2, and then deionized water is added as a solvent to prepare a negative electrode slurry with a solid content of 70%, and stirred under the action of a vacuum mixer until the system becomes a uniform negative electrode slurry. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and dried at 90°C to obtain a negative electrode sheet with a single-sided coating of negative electrode active material and a negative electrode active material layer thickness of 130μm. After the above steps are completed, the single-sided coating of the negative electrode sheet is completed. After that, the above steps are repeated on the other surface of the negative electrode sheet to obtain a negative electrode sheet with a double-sided coating of negative electrode active material. After the coating is completed, the negative electrode sheet is cold pressed and cut into a specification of 76mm×851mm for standby use. The compaction density of the negative electrode sheet is 1.8g / cm 3 .

[0070] (4) Isolation film

[0071] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0072] (5) Preparation of lithium-ion batteries

[0073] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound, the tail is glued, and placed in a punched aluminum foil bag. The edge of the aluminum foil bag is sealed, and then placed in a vacuum oven at 85°C for 12 hours to remove moisture from the dry battery cell. Finally, the prepared electrolyte is injected into the vacuum-dried battery. After vacuum packaging, standing, formation, forming and other processes, the preparation of the lithium-ion battery is completed.

[0074] Example 2 to Example 16

[0075] Except for adjusting the mass percentage of the electrolyte, the type and mass percentage of the sulfur-containing substance according to Table 1, the rest is the same as Example 1.

[0076] Comparative Examples 1 to 5

[0077] Except for adjusting the mass percentage of the electrolyte, the type and mass percentage of the sulfur-containing substance according to Table 1, the rest is the same as Example 1.

[0078] Table 1

[0079]

[0080]

[0081] Note: In Table 1, “ / ” indicates that there is no relevant preparation parameter.

[0082] It can be seen from Examples 1 to 16 that the cycle performance and safety performance of the lithium-ion battery vary with the mass percentage of the electrolyte and the sulfur-containing substances. The mass percentage of the electrolyte usually affects the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1 to 4 and Comparative Examples 1 to 2 that a lithium-ion battery with a mass percentage of the electrolyte within the range of the present application can have good cycle performance and safety performance.

[0083] The type and mass percentage of sulfur-containing substances usually also affect the cycle performance and safety performance of lithium-ion batteries. It can be seen from Examples 5 to 16 and Comparative Examples 3 to 5 that lithium-ion batteries whose types and mass percentages of sulfur-containing substances are within the scope of this application can have good cycle performance and safety performance.

[0084] Example 17 to Example 30

[0085] Except for adjusting the mass percentage of the electrolyte, the type and mass percentage of the fluorine-containing additive, and the sum of the mass percentages of the S element and the F element in the SEI film E% according to Table 2, the rest is the same as Example 1.

[0086] Comparative Example 6

[0087] Except for adjusting the mass percentage of the electrolyte, the type and mass percentage of the fluorine-containing additive, and the sum of the mass percentages of the S element and the F element in the SEI film E% according to Table 2, the rest is the same as Example 1.

[0088] Table 2

[0089]

[0090]

[0091] It can be seen from Examples 17 to 30 that the cycle performance and safety performance of the lithium-ion battery change with the change of the fluorine-containing additive. It can be seen from Examples 17 to 30 and Comparative Example 6 that the lithium-ion battery with the mass percentage of the fluorine-containing additive within the range of this application can have good cycle performance and safety performance.

[0092] It can be seen from Examples 18 to 20 and 21 to 24 that the synergistic effect of three fluorine-containing additives can better improve the cycle performance and safety performance of lithium-ion batteries.

[0093] Example 31 to Example 42

[0094] Except for adjusting the mass percentage of the electrolyte and the porosity of the positive electrode sheet according to Table 3 on the basis of Example 1, the rest is the same as Example 1.

[0095] Table 3

[0096]

[0097] It can be seen from Examples 31 to 42 that the cycle performance and safety performance of lithium-ion batteries vary with the porosity of the positive electrode plate. Lithium-ion batteries whose porosity and the ratio of porosity to electrolyte mass percentage are within the scope of this application can have good cycle performance.

[0098] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An electrochemical device, comprising a positive electrode plate, a negative electrode plate, an electrolyte and a separator, wherein the mass percentage A of the electrolyte to the total mass of the battery core is 2% to 8%; the electrolyte contains a sulfur-containing substance, and based on the total mass of the electrolyte, the mass percentage B of the sulfur-containing substance is 10% to 20%; the electrolyte includes a fluorine-containing additive, and based on the total mass of the electrolyte, the mass percentage C of the fluorine-containing additive is 15% to 30%.

2. The electrochemical device according to claim 1, wherein the sulfur-containing substance is selected from at least one of the compounds of the following formula: in, R1, R2, R3, R4, R5, R6, and R7 are each independently selected from C1 to C 10 Saturated hydrocarbon, C2 to C 10 Unsaturated hydrocarbon group, C1 to C 10 Halogenated alkyl, C2 to C 10 Halogenated alkenyl, C2 to C 10 Haloalkynyl, C6 to C 26 Any of aryl, -F, -Cl, -H; R1 and R2, R3 and R4, R5 and R6, and R7 and R8 may be connected to form a ring.

3. The electrochemical device according to claim 1, wherein The sulfur-containing substance includes at least one of 2,4-butane sultone, 1,3-propane sultone, ethylene sulfite, propylene sulfite, dimethyl sulfite, and diethyl sulfite.

4. The electrochemical device according to claim 1, wherein The fluorine-containing additive is selected from at least one of the compounds of the following formula: Wherein, X1, X2, X3, X4, X5, and X6 are each independently selected from C1 to C 10 Fluorinated saturated hydrocarbon, C2 to C 10 Fluorinated unsaturated hydrocarbon, C1 to C 10 Halogenated alkyl, C2 to C 10 Halogenated alkenyl, C2 to C 10 Haloalkynyl, C6 to C 26 Any of aryl, -F, -H; Y1 is selected from P, B, O, N or S; Y2 and Y3 are each independently selected from C1 to C 10 Fluorinated saturated hydrocarbon, C2 to C 10 Any one of fluorinated unsaturated hydrocarbon group, P, B, O, S, and N; At least one of X1 and X2, X3 and X4, X5 and X6, and Y2 and Y3 is a fluorine-containing group; X1 and X2, X3 and X4, X5 and X6, and Y2 and Y3 may be linked to form a ring.

5. The electrochemical device according to claim 1, wherein The fluorine-containing additive includes at least one of fluoroethylene carbonate, fluoroethyl methyl carbonate, fluorodimethyl carbonate, fluorodiethyl carbonate, fluoroethyl propionate, fluoropropyl propionate, fluoroethyl acetate, lithium hexafluorophosphate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium trifluoromethylsulfonate and lithium difluorophosphate.

6. The electrochemical device according to claim 1, wherein The porosity of the positive electrode plate is D%, and the value range of D is 5≤D≤35, wherein the relationship between D% and A% is as follows: 0.5≤D% / A%≤15.

7. The electrochemical device according to claim 1, wherein: The sum of the mass percentage of sulfur element and the mass percentage of fluorine element in the SEI layer on the surface of the negative electrode plate is E%, where 10≤E≤50.

8. An electronic device comprising the electrochemical device according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Electrolyte solution and battery

    CN109309256A

  • Composite electrolyte material, preparation method thereof and quasi-solid-state battery

    CN112886052A